2011
DOI: 10.1039/c1cp20800d
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and DFT study of VIVO(acac)2 in imidazolium ionic liquids

Abstract: We report the structural characterization of vanadyl acetylacetonate in imidazolium room temperature ionic liquids--bbimNTf(2), bmimNTf(2), C(3)OmimNTf(2), bm(2)imNTf(2), bmimPF(6), bmimOTf, bmimBF(4), bmimMeCO(2), bmimMeSO(4), bmimMe(2)PO(4) and bmimN(CN)(2)--and organic solvents. The complex was characterized by visible electronic (Vis) and EPR spectroscopies. VO(acac)(2) shows solvatochromism in the selected ionic liquids and behaves as in organic solvents, evidencing coordination of the ionic liquid anion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 50 publications
0
10
1
Order By: Relevance
“…Extending the observations made in molecular solvents, a scale of ionic liquid Lewis basicity is defined and compared to those reported from other electroanalytical and spectroscopic studies. 12,13,21,22 Voltammetry was measured at a platinum (d = 0.61 mm) or gold (d = 1.14 mm) macrodisk working electrode (WE), with a silver wire employed as quasi-reference electrode and a platinum foil as counter electrode. The difference in the formal redox potentials for the oxidation and reduction couples, ΔE°′, was taken directly from CVs recorded at 100 and 200 mV s −1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Extending the observations made in molecular solvents, a scale of ionic liquid Lewis basicity is defined and compared to those reported from other electroanalytical and spectroscopic studies. 12,13,21,22 Voltammetry was measured at a platinum (d = 0.61 mm) or gold (d = 1.14 mm) macrodisk working electrode (WE), with a silver wire employed as quasi-reference electrode and a platinum foil as counter electrode. The difference in the formal redox potentials for the oxidation and reduction couples, ΔE°′, was taken directly from CVs recorded at 100 and 200 mV s −1 .…”
mentioning
confidence: 99%
“…Bartosik and Mudring studied the UV−vis absorption spectroscopy of the complex [Ni(tmen)(acac)][B(Ph) 4 ] and found that the response was entirely anion dependent. 13 From the wavelength of the absorption maximum, they generated a scale of anion donor strength: 12 Attempts to correlate the trend with the Kamlet−Taft parameters failed. More recently, Schmeisser et al determined DN from the chemical shift of Na + .…”
mentioning
confidence: 99%
“…Combining the above characterization and analysis results, the possible reaction mechanism is shown in Scheme 2 and Figure 8: Light induces the formation of iodine free radicals in CHI 3 (step (3)), then I captures the electrons on Au 0 to form Au + (step (4)), which then combines with N(CN) 2 − to form AuN(CN) 2 (step ( 5)). Subsequently, the imidazole cation of the ionic liquid forms a stable [Bmim]•[Au(N(CN) 2 ) 2 ] ion pair through various intermolecular forces such as electrostatic attraction, hydrogen bonding, and cation-π bonding with AuN(CN) 2 [34][35][36] (step ( 6)).The ion-pair structure makes the metal shed from the particle surface exist in the ionic liquid in a stable form, and shifts the balance of the oxidation (step (4)) to the right, which further promotes the dissolution reaction and finally promotes the continuous dissolving of the gold particles into the ionic liquid system. In addition, the new ionic liquid BmimI obtained by ion exchange is partially precipitated in the form of crystals.…”
Section: Reaction Mechanismmentioning
confidence: 99%
“…In this regard, solvatochromism is a technique that provides relevant details about the behaviour of drugs in environments of different polarities, and in particular, about solute-solvent interactions. [7][8][9][10][11][12][13][14] This point is crucial for the research and development of novel effective drugs, which is, of course, one of the main aims of the pharmaceutical industry. In addition, understanding the influence of medium properties can provide a powerful tool to control the severity of drug toxicity and the drug efficiency in biological systems.…”
Section: Introductionmentioning
confidence: 99%